TARI ASYEIK NITI MAHLIGAI DALAM KARYA RELIEF LOGAM - Marten Agung Laksono; Asril Asril (Gorga : Jurnal Seni Rupa, 2022)
The primary steps of the asyeik niti mahligai ritual are where relief works are produced. Asyeik Niti Mahligai is performed on stage as a test by Bilian Saleh to reach the pinnacle of mysticism. The asyeik niti mahligai dance is being introduced to the public, especially the people of Kerinci, through the creation of this relief. Particularly important is the comprehension of the variations in the asyeik niti mahligai dance that is discussed in the work. The artist's version of the Asyeik Niti Mahligai  dance captures the spirit of the dance that Bilian Saleh did during the traditional procession. The second is created so that it can serve as a resource for other artists, for example, in the production of art that requires the shape of regional customs. Exploration, design, and embodiment were the strategies employed in the creation of this piece. The engraving and pressing process is employed. This two-dimensional piece uses metal reliefs to depict the procession of Bilian Saleh during the asyeik niti mahligai ceremony. Using the right-to-left reading technique, the reliefs are back in two pieces. Asyeik niti mahligai's creator relief ritual serves as a means of conserving local culture and making it accessible to future generations through artistic creations.Keywords: dance, asyeik, niti, mahligai, relief. AbstrakPenciptaan karya relief logam bersumber dari tahapan inti dalam ritual asyeik niti mahligai. Tahapan inti tersebut ialah tari asyeik niti mahligai sebagai ujian yang ditempuh bilian saleh sebagai puncak tertingi ilmu kebatinan. Tujuan penciptaan karya relief ini adalah memperkenalkan kepada masyarakat khususnya masyarakat Kerinci tentang tari asyeik niti mahligai, terutama pemahaman tentang perbedaan tari asyeik niti mahligai yang diangkat dalam karya. Tari yang angkat oleh pengkarya yaitu esensi tari asyeik niti mahligai yang dilaksanakan oleh bilian saleh pada prosesi ritual. Kedua yang diciptakan agar dapat menjadi acuan seniman lainya khususnya pada penciptaan seni rupa yang mengambil bentuk dari tradisi lokal. Metode yang digunakan dalam penciptaan karya ini ialah melalui tahapan eksplorasi, perancangan dan perwujudan. Teknik yang digunakan yaitu teknik ukir tatah dan tekan. Karya yang dihasilkan merupakan karya dua dimensi menguraikan prosesi pengangkatan bilian saleh dalam ritual asyeik niti mahligai dalam bentuk relief logam. Relief berjumlah dua karya dengan teknik membaca dari kanan ke kiri. Penciptaan relief ritual asyeik niti mahligai sebagai salah satu cara terhadap pelestarian budaya lokal agar dapat dikenal sampai generasi selanjutnya dalam bentuk karya seni rupa.Kata kunci: tari, asyeik, niti, mahligai, relief. Authors:Marten Agung Laksono : Institut Seni Indonesia Padangpanjang          Asril : Institut Seni Indonesia Padangpanjang References:Beardsley, M. (1958). Aesthetics Problem In The Philosophy Of Criticism. United states Of America: Harcourt Brace & World.Damono, S. D. (2018). Alih Wahana. Jakarta: PT Gramedia Pustaka.Gustami, S. (2007). Butir-Butir Mutiara Estetika Timur: Ide Dasar Penciptaan Seni Kriya Indonesia. Yogyakarta: Parisista.Helmiati, H., Misgiya, M., Atmojo, W. T., & Silaban, B. (2020). Eksperimen Pewarnaan Batik dengan Bahan Alami Buah Naga (Hylocereus Undatus). Gorga: Jurnal Seni Rupa, 9(1), 22-26.Daniati, N., Sastra, A. I., & Dharsono, D. (2018). Perempuan Kerinci sebagai Ide dalam Penciptaan Karya Seni Lukis. Gorga: Jurnal Seni Rupa, 7(2), 129-133.Nopia, R., Akmal, A., & Munaf, Y. (2018). KuloukKerinci dalam Karya Mahkota Putai. Gorga: Jurnal Seni Rupa, 7(2), 123-128.Putra, Eva Bramanti. (2022), “Sejarah Prosesi Ritual Asyeik Niti Mahlagi”. Hasil Wawancara Pribadi: 12 Januari 2022, Kerinci.